Testing geomorphic signal of active normal faulting: The case of the Cittanova Fault (Calabria, southern Italy). Issue 10 (15th May 2018) - Peronace, Edoardo; Della Seta, Marta; Troiani, Francesco; Galli, Paolo; Giaccio, Biagio; Messina, Paolo; Fredi, Paola
Abstract: Extracting tectonic signals from the landscape is an important challenge for constraining the style and rate of deformation associated with active faults, especially where their displacement history cannot be independently determined. Based on previous paleoseismological data coupled with new geomorphological field work and 14 C dating of geomorphic markers, we analysed the geomorphic signal of the along‐strike differential throw of the Cittanova Fault in southern Calabria (Italy), the recent activity of which is already well documented and constrained. Through DTM‐derived stream power law parameters ( SL and χ ), we provide evidence of drainage network disequilibrium and reorganization in response to fault growth and deformation style. Furthermore, a methodological test of the reliability of the χ metric as a proxy for the differential throw along the strike of active normal faults provided good preliminary results, consistent with a strong inverse linear correlation with fault throw. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : The analysis of geomorphic markers of active tectonics, footwall topography and stream longitudinal profiles allowed us to provide new evidence of the geomorphic signal of the differential throw along‐strike of the Cittanova Fault (southern Calabria, Italy). A methodological test of the reliability of the c metric as a proxy for the differential throw along the strike of active normal faults provided good preliminary results.